Gestational diabetes mellitus in women increased the risk of neonatal infection via inflammation and autophagy in the placenta. Issue 40 (2nd October 2020) - Li, Yi-xiao; Long, Deng-lu; Liu, Jia; Qiu, Di; Wang, Jingyun; Cheng, Xin; Yang, Xuesong; Li, Rui-man; Wang, Guang
Abstract: Background: Gestational diabetes mellitus (GDM) produces numerous problems for maternal and fetal outcomes. However, the precise molecular mechanisms of GDM are not clear. Methods: In our study, we randomly assigned 22 pregnant women with fasting glucose concentrations, 1 hour oral glucose tolerance test (1H-OGTT) and 2 hour oral glucose tolerance test (2H-OGTT), different than 28 normal pregnant women from a sample of 107 pregnant women at the First Affiliated Hospital of Jinan University in China. Lipopolysaccharide (LPS), interleukin 1 alpha (IL-1α), interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor alpha (TNF-α) were measured from blood plasma of pregnant women and umbilical arteries using ultraviolet spectrophotometry. Hematoxylin & Eosin (H&E), Periodic acid-Schiff (PAS) or Masson staining were performed to examine whether diabetes mellitus altered the morphology of placenta. Quantitative PCR (Q-PCR), western blotting and immunofluorescent staining were performed to examine whether diabetes mellitus and autophagy altered the gene expressions of the placental tissue. Results: We found that women with GDM exhibited increased placental weight and risk of neonatal infection. The concentrations of IL-6 protein and IL-8 protein in GDM were increased in both maternal and umbilical arterial blood. H&E, Masson and PAS staining results showed an increased number of placental villi and glycogen deposition in patients with GDM, but no placental sclerosis was found. Q-PCR results suggested that the expression levels of HIF-1α and the toll like receptor 4 (TLR4)/ myeloid differential protein-88 (MyD88)/ nuclear factor kappa-B (NF-κB) pathway were increased in the GDM placenta. Through Western Blotting, we found that the expression of NF-kappa-B inhibitor alpha (IKBα) and Nuclear factor-κB p65 (NF-κB p65) in GDM placenta was significantly enhanced. We also showed that the key autophagy-related genes, autophagy-related 7 (ATG7) and microtubule-associated protein 1A/1B-light chain 3 (LC3), were increased in GDM compared with normal pregnant women. Conclusions: Our results suggest that women with GDM exhibit an increased risk of neonatal infection via inflammation and autophagy in the placenta. Abstract : Supplemental Digital Content is available in the text